The literary construction of cognitive perception: metaphors of smell - Arslan, Fatih; Demir, Aybuke Guclu (Taylor & Francis Inc, 2025)
The forms of metaphor expression that emerge under the influence of sensory perception embody both the physiological formation of the senses of smell, taste, sight, hearing and touch and the individual and social meaning units they create in cognitive perception. In our study, odor metaphors, which are a different perception system due to the way they are perceived by the brain compared to other senses and the physiological and psychological connection they establish with human memory, are examined. First of all, examples from poetry, which is the field of literature where sense metaphors are used the most, were identified. Following this step, the existing metaphorical linguistic and semantic forms of odor expressions were identified through the Pragglejaz Group's Metaphor Identification Procedure (MIP). After identifying the source and target domains of the identified odor metaphors, their physiological and cognitive meanings and their therapeutic scope transformed into poetic therapeutic values were discussed.
Keywords: Cognitive linguistics; literature; metaphor; smell; poetry therapy